THE CULTURE OF CCN IN ISLAMIC PERSPECTIVE - Sahmiar Pulungan (Proceeding International Seminar of Islamic Studies, 2021)
An honest is an attitude that must be possessed by every human being, especially for every Muslim. Without an honest, it will be difficult to be trusted by the community. Corruption, collusions and nepotism (CCN) is known as KKN in Indonesia. It is an immoral act by abusing an authority based on a form of agreement with close people regardless of quality to get profit. CCN is a form of treason that is very large and is strictly forbidden in Islam, because this act is very dangerous. The purpose of this research was to know the form and punishment explanation of CCN values in islamic perspective. This research focused on the discussion of CCN based on Islamic perspective. The method of this research was qualitative using library research. The data used was the Qur'an and books, papers and journals related to the object of this study. then the data were analyzed using content analysis by using descriptive analytic approach to produce a comprehensive conclusion. The result of this study was the mechanism of punishment from CCN based on Islamic perspective.Keywords:Islamic Law; Corruption, Collusions; Nepotisms